Feeding difficulties in the offspring of mothers with an eating disorder - a case report - Marques, Pedro; Sá, Teresa; Martins, Vânia (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
Background: One of the main risk factors for eating disorders (ED) in early childhood is maternal ED. Mothers with a history of ED have difficulties in their approach to feeding their children, with mealtimes being perceived as stressful, with controlling behavior and intrusiveness. Case presentation: An 11-month-old female infant was evaluated at a Child Psychiatry Consultation for feeding difficulties. Her mother had a history of Restrictive Anorexia Nervosa. Mother-child psychotherapy was performed due to a pattern of insecure attachment and an ongoing conflict over control and autonomy between the caregiver-child. After the intervention, mealtimes became more natural and less conflictual. Discussion and conclusion: The authors aim to shed light on the transgenerational transmission of ED. Feeding interactions between mothers with ED and their offspring are less harmonious, with greater conflict, controlling behaviors, negative affect and decreased emotional availability to the child. Clinicians must be aware of a potential parental history of ED when dealing with children with feeding problems.